PENINGKATAN KEUNGGULAN BERSAING MELALUI STARTEGI DEERENSIASI PRODUK, INOVASI PRODUK TERHADAP KINERJA PEMASARAN PADA PRODUK UMKM JENIS PANGAN KOTA TERNATE - Ririn Damayanti; E. Ida Hidayanti; Sandi Arif (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study discusses how product differentiation, product innovation and customer relationship management affect the marketing performance of local products of MSMEs, food types in Ternate City. The purpose of this study was to examine and analyze the effect of product differentiation, product innovation with the role of competitive advantage as a mediation in influencing marketing performance. The sampling technique used a random sampling technique with a total of 190 respondents who were citizens of Ternate city, both business actors and consumers of local food products of MSMEs in the city of Ternate. The analytical test tool used is SmartPLS v.3.0 with SEM (Structural Equation Modeling) analysis method. The results of this study indicate that product differentiation not significant on competitive advantage, product innovation has a positive and significant on competitive advantage, competitive advantage has a significant effect on marketing performance,